CASE OF ACQUIRED COAGULOPATHY - M. T. Vatutin; E. S. Gasendich; E. I. Iofe (Архивъ внутренней медицины, 2018)
In recent years, the number of patients receiving anticoagulant therapy worldwide is growing rapidly. This is due to the rapidly expanding scope of their application: an increasing number of patients with non-valvular heart disease, including atrial fibrillation, the risk of thromboembolic events, an increase in the number of surgical interventions, especially in cardiac surgery (in the treatment of valvular heart disease, cardiac anomalies, infective endocarditis, staging of heart pacemakers, conducting electric cardioversion), the use of anticoagulants in the treatment of other organs and systems (in neurology, angiosurgery, obstetrics and gynecology). Despite the presence of a large number of anticoagulants in the arsenal of the modern physician, one of the most studied and often prescribed is varfarin. Warfarin is an anticoagulant of the indirect action of the coumarin group, a competitive antagonist of vitamin K. However, along with high availability and efficiency of its use, it has a large number of possible contraindications and features of the reception, such as: many drug-drug and other interactions, the need for careful control of the dosage and the regimen of the drug, strict control of the international normalized ratio throughout therapy. With caution, this drug should be used in patients who abuse alcohol and have cognitive impairment. In this group of patients, in addition to personal awareness of patients, it is necessary to conduct explanatory conversations with relatives / caregivers about all possible side effects and measures for their prevention. Non-observance of precautionary measures at therapy by warfarin can lead to heavy, and in rare instances even lethal consequences, one of which is warfarin-induced coagulopathy. This clinical case presents a case of the development of severe acquired (warfarin-induced) coagulopathy in a patient with cognitive dysfunction.